The Judicial Review Of Deed Creation And Validation Process Of Limited Liability Company On Ahu-Online Application System - Antonia Irawan; Fakhrul Wildan; Setyawati Setyawati (Jurnal Akta, 2019)
The purpose of this study are to: 1) To Detect and deploy Analyzing the Accuracy and Validation Process Limited liability company Incorporation in AHU-Online system. 2) To Know and Analyzing Barriers happened and find solutions to overcome barriers Proper case Barriers to AHU-Online System in the Process of Approval of a limited liability company (PT). The data used in this research is secondary data, which includes Legal Materials Primary, Secondary and Materials Legal Materials Tertiary Law to support the assessment which is then analyzed by Empirical Juridical approaches do with the fact that there in Practice In the field. This approach is also known by the Sociological approach made directly to the field.From the results of data analysis concluded that: 1) Accuracy and Validation Implementation in the Process of Establishment of a Limited liability company in AHU-Online system, according to the provisions of Article 9 UUPT that in order to obtain a Ministerial Decree on Approval of the Company Law Board, submitted through Online by Electronic AHU to the Minister. 2) Obstacles and Solutions in case the system is AHU-Online in the Process Ratification of a limited liability company, if it is proven the person doing the transaction was not competent law to conduct a transaction and a violation of the requirements of a particular case, and Abuse Terms of a For Halal, the Treaty of Establishment of Company can be canceled. In case of violation of the contents of the Agreement Establishing a company, it can do some act of law. If arises a problem of law and based on the Article 16 Paragraph (1) of Act No. 48 Of 2009 concerning Judicial Authority, that the court may not refuse to Check, Passing and Terminate and Judges shall Digging, Following and Understanding the Values of Law and Sense of Justice living in the community.Keywords: Judicial Review; Limited Liability Company; AHU-Online.